2018
DOI: 10.1016/j.jelechem.2018.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of a series of symmetric and asymmetric CpNiBr(NHC) complexes: Probing the electrochemical environment due to push-pull effects

Abstract: The electrochemistry of Ni(II) N-heterocyclic carbene complexes shows Ni II /Ni III oxidation, Ni II /Ni I reduction as well as NO2-ligand based reduction. Highlights  Redox processes of [CpNiBr(NHC)] complexes are both metal and ligand-based  Three oxidation states of Ni (I, II, III) are observed  Oxidation of NO2-containing complexes more positive relative to non-NO2 analogues  Redox data and DFT calculations confirm the centres associated with each process

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Both HOMO and HOMO–1 were located on the iron center; however, experimentally it was found that the second oxidation of SubPcs 5 – 8 was assigned to be SubPc ring-based instead. Since it sometimes happens that orbitals can rearrange upon oxidation, it therefore is essential to optimize the cation (oxidized) species as well, in order to computaionally locate the locus of the second experimentally observed oxidation. The oxidized SubPcs 5 – 8 all showed that their LUMO is on the iron center (first oxidation) and the HOMO and HOMO–1 of the oxidized species both are on the SubPc-ring (second and third oxidation), in agreement with the experimental assignment; see Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Both HOMO and HOMO–1 were located on the iron center; however, experimentally it was found that the second oxidation of SubPcs 5 – 8 was assigned to be SubPc ring-based instead. Since it sometimes happens that orbitals can rearrange upon oxidation, it therefore is essential to optimize the cation (oxidized) species as well, in order to computaionally locate the locus of the second experimentally observed oxidation. The oxidized SubPcs 5 – 8 all showed that their LUMO is on the iron center (first oxidation) and the HOMO and HOMO–1 of the oxidized species both are on the SubPc-ring (second and third oxidation), in agreement with the experimental assignment; see Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Upon reduction of mer molecule 1, an electron is added to the LUMO of complex 1, which is of dx2-y2 character (Figure 3). This LUMO then becomes the HOMO of the reduced molecule 1, if no re‐arrangement of the frontier orbitals occurs during reduction [31–33]. This new HOMO of the reduced mer complex 1, also shown in Figure 3, now has dx2-y2 character, while the new LUMO of reduced complex 1, as well as LUMO+1 to LUMO+10, is ligand based.…”
Section: Resultsmentioning
confidence: 89%
“…This was nicely illustrated by the occupied molecular orbital of (Figure 3). This LUMO then becomes the HOMO of the [31][32][33]. This new HOMO of the reduced mer complex 1, also shown in Figure 3, now has d x 2 À y 2 character, while the new LUMO of reduced complex 1, as well as LUMO + 1 to LUMO + 10, is ligand based.…”
Section: Dft Optimized Geometry and Properties Of Moleculesmentioning
confidence: 82%
“…However, since the top three highest occupied MOs (HOMOs) of 7-11 are all iron-d based, and Fe(III) to Fe(IV) oxidation is not expected, it was essential to also optimise the cation (oxidised) species, to locate the locus of the second experimentally observed oxidation. It is known that orbitals can rearrange upon oxidation [29][30][31]. The DFT results of oxidised SubPcs 7-11 all showed that the LUMO is of iron-d character (the first oxidation, see Figure 5) and the HOMO is on the SubPc ring (the second oxidation, see Figure 5).…”
Section: Computational Analysismentioning
confidence: 99%